CMS phase-II upgrade of the RPC Link System. (11th May 2021) - Boghrati, B.; Amoozegar, V.; Ebrahimi, M.; Ghasemi, R.; Mohammadi Najafabadi, M.; Zareian, E.; Samalan, A.; Tytgat, M.; Zaganidis, N.; Alves, G.A.; Marujo, F.; Torres Da Silva De Araujo, F.; et al.
Abstract: The present RPC Link System has been servicing as one of the CMS subsystems since installation in 2008. Although the current Link System has been functioning well for the past 13 years, the aging of its electronic components and lack of radiation hard ASICs could present problems for future operations. Additionally, the needs to have a more robust control interface against electromagnetic interference, to improve the trigger performance with finer time granularity and to incorporate a higher bandwidth transmission lines led the idea of upgrading the Link System for the HL-LHC. This paper reviews the features of the recently developed prototype of the new Link System.